Six‐face cubical key encryption and decryption based on product cipher using hybridisation and Rubik's cubes. Issue 5 (1st September 2018) - Dhandabani, Rajavel; S. Periyasamy, Shantharajah; Theagarajan, Padma; Sangaiah, Arun Kumar
Abstract : This paper deals with the novel approach to generate cubical key that symbolises the message and key in six‐face cubical structure. The cubical message is hybridised to generate the cipher in the encryption. Hybridisation of cubes is performed by using the XOR operation to the six‐face cubical original message and six‐face random sequence which is a part of Key‐Cube. Key‐Cube consists of Rotation Type (RT‐Cube), Rotation Angle (RA‐Cube) and Random Sequence (R‐Cube). As a product cipher technique we generate the S‐Cube and P‐Cube in each of the iterations and it symbolises the substitution and permutation, respectively. Here, total 36 round phase is carried out to generate the final cipher. To guarantee the randomness in each phase of hybridization, cubical message and cubical form of random sequence are shuffled in each of the iterations based on RA‐Cube and RT‐Cube. Cubical message representation, cube hybridisation and shuffling the message using Rubik Cube technique ensure the security hardness in the final cipher. We analysed the strength of our proposed approach by compared the cipher variance with the original message and analysed our encryption technique with well‐known block cipher attaches. The results and analysis show betterment in our proposed approach.